Diagnostic accuracy of HE4 and risk of ovarian malignancy algorithm in prediction of ovarian cancer in patients with pelvic mass: a regional cancer centre experience - Arora, Ruchi S.; Patel, Shilpa M.; V., Abhilash; Vemanamandhi, Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The current study was performed with an objective to evaluate the diagnostic accuracy of HE4 (human epididymis protein) and ROMA in prediction of ovarian cancer in patients with pelvic mass and to compare HE4 and ROMA with CA-125, and RMI (risk of malignancy index) for ovarian cancer prediction in women with pelvic mass. Methods: This was a diagnostic study enrolling 200 patients with pelvic mass who had been scheduled for Primary surgery. Serum HE4 and CA 125 levels were measured. HE4, CA 125 and ROMA, RMI were evaluated for sensitivity, specificity, positive predictive value and negative predictive value. The receiver operating characteristic (ROC) plots were graphed and area under the curve (AUC) values was calculated to investigate the accuracy of each marker for predicting ovarian malignancy. Results: Overall, ROMA showed the highest accuracy as it correctly classified 139/200 (69.5%) patients compared with 133/200 (66.5%) in HE4 and 109/200 (54.5%) in CA 125 and RMI. There were more patients with benign tumors being correctly identified by HE4 (89/119, 74.7%) and ROMA (74/119, 62.1%), than CA 125 which identified 39/119 (32.7%) patients. In our study in premenopausal women ROMA and HE4 have comparable sensitivity (80%and 75%) but higher specificity (64% and 65%) and NPV (86% and 83%) as compared to CA125 which has sensitivity of (83%) but very low specificity (46%) in differentiating benign from malignant masses. In postmenopausal women, HE4 had highest specificity (88%) and, CA125 has highest sensitivity (86%) in detecting ovarian malignancy. Conclusions: HE4 and ROMA showed a high specificity, but were less sensitivity than CA-125 and RMI in premenopausal women. However, ROMA is of comparable sensitivity and HE4 has highest specificity as compared to CA125 in postmenopausal women.